THE PHILOSOPHY OF EDUCATIONAL MANAGEMENT: FINDING A NEW DIRECTION FOR SCHOOL LEADERSHIP IN THE ERA OF DISRUPTION - Mahdi, Mahdi; Hidayat, Nandang (Yayasan Amanah Nur Aman, 2025)
The era of disruption has brought significant changes to educational management systems and demands school leadership that is adaptive, reflective, and grounded in philosophical values. However, the practical orientation of education has often overlooked the philosophical foundations that should guide thinking and strategic decision-making in educational leadership. This study aims to examine the essence of the philosophy of educational management as a conceptual basis for an adaptive school leadership model in the disruption era. This research employs a qualitative approach using the library research method. Data were obtained from books, national and international scholarly journals, and educational policy documents relevant to the theme of the philosophy of educational management. The data were analyzed through three stages: data reduction, data presentation, and reflective conclusion drawing using ontological, epistemological, and axiological approaches. The findings indicate that the philosophy of educational management functions as a conceptual framework that guides school principals in understanding the nature of human beings, knowledge, and values in leadership practice. The integration of these three philosophical dimensions produces a reflective leadership model that emphasizes a balance between managerial rationality, morality, and spirituality. The results affirm that the philosophy of educational management can serve as a foundation for school leadership that is oriented toward humanity and value transformation amid technological and social change. The implications of this study highlight opportunities for developing value-based leadership models to address the complexities of the disruption era.